Dynamic Modeling and Residual Vibration Suppression of the Redundantly-Actuated Cable Driving Parallel Manipulator - Zhengsheng Chen; Xuesong Wang (IEEE Access, 2020)
An improved input shaping (IS) scheme was proposed for the redundantly actuated cable driving parallel robots (CDPRs) to suppress the residual vibration (RV). To make the design of the RV suppression convenient, the flexible displacements of the moving platform were taken as the generalized coordinates considering the axial deformation of cables, and rigid-flexible dynamic model of generalized redundantly actuated CDPRs was established with the Newton-Euler equation and the Newton's law. Then to cope with time-variant vibration frequencies of the CDPRs due to the variable lengths of cables, the technique that combined the one- to three-order zero vibration (ZV) IS with the particle swarm optimization (PSO) and the controller was proposed to suppress the RV. At last, to validate the effectiveness the proposed method, the simulations were carried out in a redundantly actuated CDPR that has six degree-of-freedom CDPR and seven driving cables with the proposed method, the results show that the RVs can be reduced significantly.